2019
DOI: 10.1097/md.0000000000014954
|View full text |Cite
|
Sign up to set email alerts
|

Association between RUNX3 gene polymorphisms in severe preeclampsia and its clinical features

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Since rs7528484 was firstly reported to involve in gastric cancer risk, 13 only one study reported a positive genetic association between rs7528484 and severe preeclampsia. 14 However, the association between RUNX3 rs7528484 and CRC susceptibility is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Since rs7528484 was firstly reported to involve in gastric cancer risk, 13 only one study reported a positive genetic association between rs7528484 and severe preeclampsia. 14 However, the association between RUNX3 rs7528484 and CRC susceptibility is still unclear.…”
Section: Introductionmentioning
confidence: 99%